Metal-Free Synthesis of Thiocyanated Aminonitroalkenes and 2-Aminothiazoles/selenazoles from β-Aminonitroalkenes and N‑Thio/Selenocyanatosaccharin - Yang, Hongchen; Chen, Yuce; Xu, Xiaoyong; Li, Zhong (Synlett, 2022)
A convenient and efficient protocol has been developed for the synthesis of thiocyanated aminonitroalkenes and 2,4,5-trisubstituted thiazoles/selenazoles from β-aminonitroalkenes and N‑thio/selenocyanatosaccharin. This method features simple operation, mild reaction conditions, short reaction time, good functional group compatibility, and metal-free characteristics. The broad applications of polysubstituted thiazoles/selenazoles in organic and medicinal chemistry make this protocol much more practical.
Keywords: 2-aminothiazoles; β-aminonitroalkenes; N‑thiocyanatosaccharin